Various clinical factors’ influence on long-term results of valve prosthetic surgery in heart valve disease - L. I. Murzabekova; V. A. Orlov (Кардиоваскулярная терапия и профилактика)
Aim. To assess factors influencing the long-term results of valve prosthetic surgery in heart valve disease. Material and methods. In total, 310 patients with heart valve surgery in anamnesis were examined: 168 females (54%), 142 males (46%); mean age 54.2±1.6 years. The most frequent cause of heart valve pathology was rheumatism (n=248; 80%); infectious endocarditis (n=49; 16%) and primary valvular degeneration (n=13; 14%) were less common. Patients’ status was assessed by NYHA classification and the Duke Activity Status Index; their quality of life (QoL) – by general methods (Medical Outcomes Study, 36-Item Short Health Survey, Nottingham Health Profile) and disease-specific instruments (Minnesota Living with Heart Failure Questionnaire, Kansas City Cardiomyopathy Questionnaire). To assess the association between individual parameters, Pearson linear correlation analysis was used. Results. Most participants underwent mitral valve prosthetic surgery, with mechanical prosthesis implantation. Comparing to biological prosthesis implantation, the rates of re-operation, thromboembolia, prosthetic infectious endocarditis, paravalvular fistules were higher. The factors associated with long-term adverse outcomes were: prosthetic infectious endocarditis, mechanic prosthesis implantation, and left atrium thrombosis in post-surgery period. Moreover, these factors negatively affected subjective QoL parameters. Conclusion. Correlation analysis can be used for assessing long-term results of heart valve prosthetic surgery.